Working memory processes and the histamine-3 receptor in schizophrenia: a [11C]MK-8278 PET-fMRI study - Atheeshaan Arumuham; Ekaterina Shatalina; Matthew M. Nour; Mattia Veronese; Ellis Chika Onwordi; Stephen J. Kaar; Sameer Jauhar; Eugenii A. Rabiner; Oliver D. Howes (Psychopharmacology, 2025)
Rationale Working memory impairment is a prominent feature of schizophrenia which predicts clinical and functional outcomes. Preclinical data suggest histamine-3 receptor (H3R) expression in cortical pyramidal neurons may have a role in working memory, and post-mortem data has found disruptions of H3R expression in schizophrenia. Objectives We examined the role of H3R in vivo to elucidate its role on working memory impairment in schizophrenia. Methods We used positron emission tomography (PET) with the selective H3R radioligand [ 11 C]MK-8278 to measure H3R availability, and employed a task during functional magnetic resonance imaging (fMRI) to assess working memory-evoked brain activation and cognitive task performance, in patients with schizophrenia ( n = 12) and matched healthy volunteers ( n = 12). We assessed the relationship between H3R availability and both task performance and working memory-evoked brain activation in regions of interest (ROIs), including the anterior cingulate cortex (ACC) and dorsolateral prefrontal cortex (DLPFC). Results Patients with schizophrenia showed a strong positive correlation, after corrections for multiple comparisons, between ACC H3R availability and task performance (rho = 0.73, p = 0.007), which was absent in the control group (rho = 0.03, p = 0.94). Further ROI analysis did not find a significant relationship between H3R availability and working memory-evoked brain activation. Conclusions These results provide support for the role of H3R on working memory processes in patients with schizophrenia.